2(7x-6)-3x=11x-17

Simple and best practice solution for 2(7x-6)-3x=11x-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7x-6)-3x=11x-17 equation:



2(7x-6)-3x=11x-17
We move all terms to the left:
2(7x-6)-3x-(11x-17)=0
We add all the numbers together, and all the variables
-3x+2(7x-6)-(11x-17)=0
We multiply parentheses
-3x+14x-(11x-17)-12=0
We get rid of parentheses
-3x+14x-11x+17-12=0
We add all the numbers together, and all the variables
5!=0
There is no solution for this equation

See similar equations:

| 8.5x-16.2=60.3 | | (5x+1)+(3x+15)=180 | | 6k+10k=-16 | | X=17(180-x) | | 12-x/5=6 | | 75-36+m=180 | | 5+(2/7)x=-9* | | 5(x-6)=-150 | | 4(x+12)=x+15 | | 2x^2+12/x=5x | | 3(2x+4)=4x+12+3x | | 75-36=x | | 6x-9=4x0-1 | | 7.p=245 | | 8x-11=x-32 | | Y=-8+6-5-y=-6 | | 19+13y=32* | | 5z^2-9=41+3z^2 | | -3x+23=8x+1 | | 5x-7=-7* | | -3h+7=5h-33 | | -1.3+2.7=2.y | | 5(3w+3)=3(3w+5) | | -8+8g=56* | | -2x+25=7x+10 | | 5(3w+3)=3(3w+5 | | x=29(180-x) | | 0.5+13=4(x-2) | | 18x-36=15(x+305) | | 17+s=18 | | 5/8(5x+9)=23 | | -n+1=11* |

Equations solver categories